Implementing Quizlet in Teaching Vocabulary Achievement for 5th Grade Students - Ningsih, Kadek Wiwin Dwipajaya; Padmadewi, Ni Nyoman; Dewi, Kadek Sintya (Universitas Pendidikan Ganesha, 2024)
Elementary school students have not been able to master basic vocabulary, so many have difficulty learning English. Students have difficulty in translating, understanding, and pronouncing words, as well as spelling and remembering vocabulary, so their interest in learning English decreases. This study aims to analyze the implementation of Quizlet in the English vocabulary achievement of 5th-grade elementary school students. This study uses a quasi-experimental method with a post-test-only control group design. The sampling technique used is total sampling. The entire population of 5th-grade students consists of two parallel classes. The data collection method uses tests. The data collection instrument uses test questions. The data analysis technique uses inferential statistical analysis (t-test). The results of this study show that the mean post-test value of the experimental group is higher than the control group. The results of the t-test show significant values between the two groups. The calculation of the effect size also supports this by showing Cohen's large standard. It is concluded that the use of Quizlet is efficacious in improving students' English vocabulary achievement. This study implies that the application of Quizlet in vocabulary achievement in English learning helps increase students' interest in learning.